WHAT ARE PRECEDENTS AND HOW SHOULD JUDGES HANDLE THEM? CONSIDERATIONS BASED ON THE JURISPRUDENCE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Popović, Dragoljub (Pravni zapisi, 2017)
The Practice Statement of the House of Lords of 1966 posed the principle for the use of precedent in English law. The European Court of Human Rights developed its own stance on the authority of precedent in various judgments. The positions of the two jurisdictions on the issue are substantially the same. The precedents are to be followed and their authority is binding for the courts.